Passive thermal management systems employing hydrogel for the large-format lithium-ion cell: A systematic study. (15th September 2021) - Wu, Nan; Ye, Xiaolin; Li, Junjie; Lin, Boshen; Zhou, Xuelong; Yu, Bin
Abstract: The large-format lithium-ion cells are growing in popularity as high-energy-density power sources in mobile applications, which calls for efficient and compact passive thermal management systems. Hydrogel, capable of absorbing and holding extremely large amounts of water, emerges as a new type of heat sink material. Herein, we presented a systematic study on the passive thermal management systems employing hydrogel for the 20 Ah large-format lithium-ion cell with emphasis on regulating the temperature homogeneity and temperature spike. Four types of configurations were designed and experimentally explored to achieve optimal cooling performance. It showed that introducing heat conducting plate between hydrogel and battery surface can effectively improve the temperature homogeneity, and the highest temperature and largest temperature difference were controlled to be only 40.5 °C and 2.5 °C even under a high discharge rate of 4C, which were about 2.5 °C and 2.3 °C lower than the pure hydrogel system. In addition, heat dissipation fins and copper foam were also employed to further accelerate the heat transfer process within the hydrogel. It showed that the fin-hydrogel system held the best performance and delivered a maximum surface temperature and a largest temperature difference of 32.6 °C and 1.4 °C over eight 3C/1C discharge/charge cycles. Highlights: Four hydrogel-based cooling architectures are explored for large-format batteries. Temperature homogeneity is enhanced by the indirect-contact structure. Fin-hydrogel system affords the best cooling performance. Temperature spike and temperature gradient are well controlled even at 4C. Sustainable cooling capability of the hydrogel systems is validated over cycles.